Insignificant impact of prescribed fire on surface soil in a Pinus pinaster plantation, northern Portugal - Meira Castro, Ana C. (2014)
Following a prescribed fire in a Pinus pinaster forest site located in the north-west Portugal, monitoring of any changes in selected soil characteristics and soil hydrology was undertaken to assess the effects of burning on the following: pH, electrical conductivity, water content, organic carbon and porosity. Thirty plots were established on a regular grid. At each sample plot before and after the fire, samples were collected (disturbed samples from depths of 0-1cm and 1-5cm; undisturbed core samples from 0-5cm). The results indicate that there was no measurable impact on the properties of the soil following this carefully conducted prescribed fire. The fire only affected the litter layer, as intended. Confirmation of this minimal impact on the soil was provided by regrowth of grasses and herbs already occurring two months after the fire. The implication is, therefore, that provided this wildfire-risk reduction strategy is carried out under existing strict guidelines, any impact on soil quality will be minimal.